CORRECTIVE LIPOFILLING IN PATIENTS WITH BREAST CANCER AFTER COMBINED TREATMENT - A. D. Zikiryakhodzhayev; A. A. Masri; A. S. Sukhotko; M. V. Starkova; N. V. Ablitsova; F. N. Usov; V. V. Ratushnaya; N. V. Evtyagina (Исследования и практика в медицине, 2018)
Breast cancer (BC) takes the first place in the structure of morbidity and mortality among the female population. One of the main methods of treating the disease is surgical one, it can lead to both complete removal of the breast and partial tissue damage. In most cases, the further socially active behavior of the patient depends on the quality of the performed operation.In this article, two clinical cases of corrective lipofilling at the final stage of reconstructive and plastic surgeries in patients with breast cancer after complex treatment are presented. Specifi c examples showed a positive effect after a single lipofilling session of the formed breast using both syringe and water jet techniques. This procedure is carried out to improve the cosmetic results in patients after comprehensive treatment for breast cancer.It is proved that mesenchymal stromal cells, or messenger cells present in all fatty tissues, promote its regeneration by forming new blood vessels or directly affect damaged or susceptible structures — restore and rejuvenate the areas of lipofilling. Therefore, adipose tissue is a natural source of regeneration of the human body. On these clinical examples, after a successful one lipophilic session, improvement of the quality of the skin in the reconstructed breast area was noted and, as a result, a good cosmetic result after reconstructive plastic surgery, both in the patient with the use of a silicone endoprosthesis and without it.